1986
DOI: 10.1002/ijc.2910370105
|View full text |Cite
|
Sign up to set email alerts
|

Parity and breast cancer risk: Possible effect on age at diagnosis

Abstract: We examined the effect of parity on breast cancer risk on the basis of information from 107,146 married female nurses followed prospectively between 1976-1980. For everparous women, a significant protective effect against breast cancer was observed with increasing parity (chi 12 for trend = 14.2, p less than 0.001). Adjustment for age at first birth and other potential confounders by multiple logistic regression did not materially affect this trend. After controlling for these risk factors, the overall relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
4

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 24 publications
4
35
4
Order By: Relevance
“…Our data did not support either the hypothesis of a cross-over effect of parity (Janerich & Hoff, 1982;Pathak et al, 1986;Negri et al, 1988) -with increased relative risks at younger ages and a protective effect in older women -or the finding of a rising risk with increasing number of births in premenopausal women (Brignone et al, 1987). Moreover, recent claims that induced abortions (Pike et al, 1981;Hadjimichael et al, 1986;Ewertz & Duffy, 1988), a long interval between menarche and first birth (Brignone et al, 1987), and a last pregnancy at a high age (La Vecchia et al, 1987) entail an increased risk was given no support.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Our data did not support either the hypothesis of a cross-over effect of parity (Janerich & Hoff, 1982;Pathak et al, 1986;Negri et al, 1988) -with increased relative risks at younger ages and a protective effect in older women -or the finding of a rising risk with increasing number of births in premenopausal women (Brignone et al, 1987). Moreover, recent claims that induced abortions (Pike et al, 1981;Hadjimichael et al, 1986;Ewertz & Duffy, 1988), a long interval between menarche and first birth (Brignone et al, 1987), and a last pregnancy at a high age (La Vecchia et al, 1987) entail an increased risk was given no support.…”
Section: Discussioncontrasting
confidence: 92%
“…A closer view of available data, however, often reveals a pattern of contradictory findings rather than consistent ones. For instance, the duration of breast feeding and the number of children became accepted as proxy variables for age at first birth almost two decades ago (MacMahon et al, 1973;Kelsey, 1979), whereas later evidence indicates that both breast feeding and high parity exert independent protective effects against the development of breast cancer (Tulinius et al, 1978;Adami et al, 1980;Paffenbarger et al, 1980;MacMahon et al, 1982;Brinton et al, 1983;Helmrich et al, 1983;Trapido, 1983;Lipnick et al, 1984;Byers et al, 1985;Pathak et al, 1986;Ewertz & Duffy, 1988;La Vecchia et al, 1987;Layde et al, 1989).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiologic studies of breast cancer risk have identified numerous host and environmental determinants (1-13) that presumably play an etiologic role in the development of the disease. While the majority of these studies have used case-control designs (1)(2)(3)(4)(5)(6)(8)(9)(10)(11), a few cohort studies have been reported, though none have involved an essentially representative sample of women from the United States (7,12,13).…”
mentioning
confidence: 99%